2013
DOI: 10.1515/znc-2013-11-1209
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a cDNA Library from the Ephemeral Plant Olimarabidopsis pumila and Preliminary Analysis of Expressed Sequence Tags

Abstract: Olimarabidopsis pumila is a close relative of the model plant Arabidopsis thaliana but, unlike A. thaliana, it is a salt-tolerant ephemeral plant that is widely distributed in semi-arid and semi-salinized regions of the Xinjiang region of China, thus providing an ideal candidate plant system for salt tolerance gene mining. A good-quality cDNA library was constructed using cap antibody to enrich full-length cDNA with the gateway technology allowing library construction without traditional methods of cloning by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…The titer of the original and amplified library of the cotton roots were 1.22×10 6 PFU mL -1 and 10 8 PFU mL -1 respectively. Earlier studies reported that titer of cDNA library of root 1.6×10 6 PFU mL -1 (Zhao et al, 2013) which support our results. The data generated by EST's of randomly selected transcripts isolated under specific stress factors provide a chance to explore gene function and their category besides their different physiological progressions in plants against different stresses (Wong et al, 2005).Genomic approaches may help in understanding the physiological events at cellular and molecular level by dissecting the genetic resources of plants (Chaves et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…The titer of the original and amplified library of the cotton roots were 1.22×10 6 PFU mL -1 and 10 8 PFU mL -1 respectively. Earlier studies reported that titer of cDNA library of root 1.6×10 6 PFU mL -1 (Zhao et al, 2013) which support our results. The data generated by EST's of randomly selected transcripts isolated under specific stress factors provide a chance to explore gene function and their category besides their different physiological progressions in plants against different stresses (Wong et al, 2005).Genomic approaches may help in understanding the physiological events at cellular and molecular level by dissecting the genetic resources of plants (Chaves et al, 2003).…”
Section: Discussionsupporting
confidence: 92%